Organizational strategy and resource-allocation for technological turnaround - MOENAERT, Rudy K. (Institutional Knowledge at Singapore Management University, 1990)
A major issue for organizations planning for technological turnaround concerns the question of how to internalize the new technology. This article reports the findings of an exploratory research that addressed this problem. A multiple case study approach has been used to study and analyze the different strategies and organizational approaches to absorb alien technologies (in-house development, intercompany co-operation, purchase of technology, contract research, joint-venture, acquisition). On the basis of the results, a propositional framework has been developed which offers managers a perspective to develop a strategy with respect to the appropriate organizational design to ‘de-mature’ technologically mature business units.